Barriers to and facilitators of physical activity among Saudi adults: a qualitative study - Albujulaya, Naif; Stevinson, Clare (Frontiers in Psychology, 2025)
IntroductionPhysical activity is widely recognized as a cornerstone of population health and well-being, yet various barriers might hinder participation in the Kingdom of Saudi Arabia despite the Saudi government efforts to promote exercise. This study aimed to explore in depth the factors influencing physical activity, with a particular focus on outdoor exercise.MethodsThe study employed snowball sampling through a social media platform to recruit Saudi men and women aged 18 years or more. Exclusion criteria include individuals under 18, with disabilities or vulnerabilities, or without access to a phone or internet-connected device for interviews. Twenty-two semi-structured interviews were conducted, and data were analyzed using qualitative content analysis.ResultsFindings identified societal and environmental barriers, including discouragement from others, poor facilities, and unsafe environments, negatively impacted exercise behavior, particularly among women. Despite these barriers, personal motivations, such as improving health and mental well-being, and community engagement were identified as significant motivations to physical activity.ConclusionThe evidence from this study suggest that targeted strategies and polices (at local and national level) addressing environmental and social constraints, combined with promoting community and health-based initiatives, can enhance physical activity and outdoor exercise participation in the Kingdom of Saudi Arabia.